Hadiths about the status of scholars "An analytical study" (Journal of the College of Basic Education, 2026)
This research addresses the topic of human development from the perspective of the Prophetic Sunnah. It highlights how the Sunnah provides an integrated framework for building human beings and developing their physical, psychological, spiritual, and social capabilities to enable them to become effective members of society.The most prominent components of human development in light of the Sunnah were reviewed, such as: faith in God and trust in Him, effective time management, personal skills development (self), and awareness development.The research also addressed the paths to success in human development through the guidance of the Prophet (peace and blessings be upon him) and his practical approach in motivating his companions and enabling them to discover themselves and develop their abilities.The research concluded that the Prophetic Sunnah represents a balanced approach that combines value-building, self-development, and achievement. Returning to this Sunnah is essential for a deeper and more comprehensive understanding of true development, which combines material and spiritual aspects.